Silicon-carbon negative electrode material and preparation method and application thereof

By using thermochemical vapor deposition method in silicon-carbon composite materials to grow carbon nanofibers and vertical graphene, a multi-layer three-dimensional network structure is formed, which solves the problem of volume expansion and poor interface contact during circulation, and improves the Conductivity and cyclic stability achieve efficient carrier transport and solid electrolyte interface stability.

CN119170791AActive Publication Date: 2024-12-20SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411058034.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2024-12-20
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

Silicon-carbon composite materials are broken due to the expansion of nano-silicon particles during the circulation process, which affects the stability of the solid electrolyte membrane and carrier transmission efficiency. It is difficult for traditional processes to obtain uniformly distributed high-load silicon-carbon composite materials, silicon and carbon materials. Poor interface contact.

Method used

Thermochemical vapor deposition method is used to grow carbon nanofibers and vertical graphene on porous carbon fiber membranes supported by metal catalysts, forming a multi-layer three-dimensional network structure, tightly covering nanosilicon-based materials, and improving the conductivity and cyclic stability of silicon carbon negative electrode materials sex.

Benefits of technology

The three-dimensional network structure relieves the volume expansion of silicon-based materials, improves the structural and cyclic stability of silicon-carbon negative electrode materials, enhances carrier transmission, promotes the stable formation of solid electrolyte interface phases, and improves conductivity and capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170791A_ABST
    Figure CN119170791A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a silicon-carbon negative electrode material and a preparation method and application thereof. Comprising the following steps: preparing a porous carbon fiber membrane loaded with a metal catalyst; preparing dispersion liquid of a nano silicon-based material, and distributing the nano silicon-based material into the porous carbon fiber membrane to obtain a composite porous carbon fiber membrane; and performing thermal chemical vapor deposition on the composite porous carbon fiber membrane in an inert atmosphere containing a carbon source, so that carbon nanofibers and vertical graphene grow on the surface of the composite porous carbon fiber membrane to obtain the silicon-carbon negative electrode material. Through a synthetic route of thermal chemical vapor deposition (T-CVD), a synthetic process is optimized, and a multi-layer three-dimensional network structure of carbon nanofibers and vertical graphene is constructed, so that the conductivity of the silicon-carbon negative electrode material is enhanced, carrier transport is accelerated, the interface contact performance between a silicon-based material and a carbon material is improved, the loading capacity of the nano silicon-based material is improved, and the service life of the silicon-carbon negative electrode material is prolonged. The volume expansion is inhibited, and the structure and cycle stability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and in particular relates to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] With the rise of electric vehicles and portable electronic devices, the market demand for efficient and safe lithium-ion batteries (LIBs) has surged. Advanced anode materials play a key role in improving their performance, especially in terms of capacity, cycle life, and energy density. However, the limited theoretical capacity of graphite anodes (372 mAh g -1 ) and insufficient rate performance limit their application in next-generation energy storage devices. To overcome this obstacle, extensive research has been conducted to develop novel anode materials, including lithium metal, SnO2, TiO2, Li4Ti5O 12 However, these new anode materials have challenges such as lithium metal dendrite formation, short cycle life of tin-based materials, poor conductivity of titanium-containing compounds, and complex manufacturing process and high cost of transition metal nitrides.

[0003] Among various negative electrode materials, silicon (Si) has a high theoretical specific capacity (3579 mAh g -1 ), low electrochemical potential for lithium insertion / extraction (<0.5V versus Li / Li + ), low price, and abundant natural resources make it a promising competitor for the next generation of lithium-ion batteries. However, the nearly 300% volume expansion of silicon during lithiation and delithiation produces great mechanical stress. After many cycles, silicon particles will break and shatter, resulting in the formation of an unstable solid electrolyte interface phase and loss of electrical contact, ultimately leading to rapid capacity decay and negative electrode failure. In order to meet these challenges, various strategies have been explored to rationally design and manufacture new silicon-based anode materials, and various advanced silicon-carbon composites have been developed, such as silicon-amorphous carbon, silicon-graphene, silicon-carbon nanotubes, silicon-graphite, silicon-carbon nanofibers, etc.

[0004] However, silicon-carbon composites still face some key problems, such as: the volume expansion of nano-silicon particles during the cycle causes silicon particles to break and pulverize, affecting the stability of the solid electrolyte membrane (SEI); the difficulty in obtaining uniformly distributed high-load silicon-carbon composites in traditional processes; and the poor interface contact between silicon and carbon materials, which limits the transmission of electrons and ions in silicon-carbon composites. Summary of the invention

[0005] The purpose of the present application is to provide a silicon-carbon negative electrode material and a preparation method and application thereof, aiming to solve to a certain extent the problems of poor interface contact between silicon and carbon materials and large volume expansion of silicon particles in the silicon-carbon negative electrode material prepared by the existing process, resulting in poor stability of the solid electrolyte interface and poor carrier transfer efficiency.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application provides a method for preparing a silicon-carbon negative electrode material, comprising the following steps:

[0008] preparing a porous carbon fiber membrane loaded with a metal catalyst;

[0009] Preparing a dispersion of nano silicon-based materials to distribute the nano silicon-based materials into the porous carbon fiber membrane to obtain a composite porous carbon fiber membrane;

[0010] In an inert atmosphere containing a carbon source, the composite porous carbon fiber membrane is subjected to thermal chemical vapor deposition to grow carbon nanofibers and vertical graphene on the surface of the composite porous carbon fiber membrane to obtain a silicon-carbon negative electrode material.

[0011] In some possible implementations, the step of preparing a porous carbon fiber membrane loaded with a metal catalyst includes: preparing a solution of the metal catalyst, infiltrating a porous carbon fiber substrate into the solution of the metal catalyst, and drying to obtain the porous carbon fiber membrane loaded with the metal catalyst.

[0012] In some possible implementations, the metal catalyst includes at least one of a cobalt catalyst, a nickel catalyst, a copper catalyst, and a platinum catalyst.

[0013] In some possible implementations, the metal catalyst includes at least one cobalt catalyst selected from the group consisting of cobalt acetylacetonate, cobalt acetate, and cobalt chloride.

[0014] In some possible implementations, the porous carbon fiber substrate includes at least one of carbon felt, graphite paper, graphite plate, and carbon fiber cloth.

[0015] In some possible implementations, the concentration of the metal catalyst solution is 40 mg / mL to 60 mg / mL.

[0016] In some possible implementations, the diameter of the fibers in the porous carbon fiber substrate is 5 μm to 15 μm.

[0017] In some possible implementations, the porous carbon fiber membrane has a thickness of 0.5 mm to 1.5 mm.

[0018] In some possible implementations, in the solution of the metal catalyst, the solvent includes at least one of methanol, ethanol, acetone, benzene, isopropanol, and n-hexane.

[0019] In some possible implementations, the preparation of the composite porous carbon fiber membrane includes the steps of: preparing a dispersion of the nano-silicon-based material, distributing the nano-silicon-based material in the dispersion into the porous carbon fiber membrane by filtering, and obtaining the composite porous carbon fiber membrane.

[0020] In some possible implementations, in the dispersion of the nano-silicon-based material, the solvent includes at least one of methanol, ethanol, acetone, benzene, isopropanol, and n-hexane.

[0021] In some possible implementations, in the dispersion of the nano-silicon-based material, the mass percentage of the nano-silicon-based material is 5% to 50%.

[0022] In some possible implementations, the nano silicon-based material includes at least one of elemental silicon, silicon oxide, and silicon carbide.

[0023] In some possible implementations, the particle size D50 of the nano-silicon-based material is 30 nm to 200 nm.

[0024] In some possible implementations, the loading amount of the nano-silicon-based material in the composite porous carbon fiber membrane is 1 mg / cm 2 ~40mg / cm 2 .

[0025] In some possible implementations, in the inert atmosphere, the carbon source includes at least one of ethanol, acetone, benzene, methanol, isopropanol, and n-hexane.

[0026] In some possible implementations, the inert atmosphere includes at least one inert gas selected from the group consisting of argon, nitrogen, and helium.

[0027] In some possible implementations, the inert atmosphere further includes an etching gas.

[0028] In some possible implementations, the etching gas includes at least one of hydrogen, oxygen, and hydrogen fluoride.

[0029] In some possible implementations, in the inert atmosphere, the flow rate of the inert gas is 100 mL / min to 180 mL / min; the flow rate of the carbon source gas is 100 mL / min to 180 mL / min; and the flow rate of the etching gas is 100 mL / min to 150 mL / min.

[0030] In some possible implementations, the heating rate of the thermal chemical vapor deposition is 5° C. / min to 10° C. / min, the holding temperature is 1000° C. to 1200° C., and the holding time is 6 h to 12 h.

[0031] In some possible implementations, the method further includes the following steps: after growing the carbon nanofibers and the vertical graphene, naturally cooling to 600° C. to 900° C., and performing a nitrogen doping reaction with a nitrogen source gas to obtain a nitrogen-doped silicon-carbon negative electrode material.

[0032] In some possible implementations, the nitrogen source gas includes at least one of ammonia, nitric oxide, and urea.

[0033] In some possible implementations, the flow rate of the nitrogen source gas is 15 mL / min to 25 mL / min.

[0034] In some possible implementations, the nitrogen doping reaction takes 20 minutes to 40 minutes.

[0035] In some possible implementations, the step of thermal chemical vapor deposition includes: under the condition that the flow rate of the inert gas is 100mL / min~180mL / min, after heating to 1000℃~1200℃ at a heating rate of 5℃ / min~10℃ / min, introducing the carbon source and the etching gas and keeping the temperature for 6h~12h to grow the carbon nanofibers and the vertical graphene; naturally cooling to 600℃~900℃, introducing the nitrogen source gas at a flow rate of 15mL / min~25mL / min to react for 20min~40min to obtain the nitrogen-doped silicon-carbon negative electrode material.

[0036] In a second aspect, the present application provides a silicon-carbon negative electrode material, comprising a porous carbon fiber substrate and a nano-silicon-based material loaded in the porous carbon fiber substrate, wherein the surface of the nano-silicon-based material is coated with carbon nanofibers and vertical graphene.

[0037] In a third aspect, the present application provides a negative electrode sheet, which includes the silicon-carbon negative electrode material prepared by the above method, or the above silicon-carbon negative electrode material.

[0038] In a fourth aspect, the present application provides a secondary battery comprising the above-mentioned negative electrode sheet.

[0039] The first aspect of the present application provides a method for preparing a silicon-carbon negative electrode material. After preparing a porous carbon fiber membrane loaded with a metal catalyst, a nano-silicon-based material is distributed into the porous carbon fiber membrane to form a composite porous carbon fiber membrane with a double layer of metal catalyst and nano-silicon-based material. Then, in an inert atmosphere containing a carbon source, the composite porous carbon fiber membrane is subjected to thermal chemical vapor deposition to grow carbon nanofibers (CNFs) and vertical graphene (VGs) on the surface of the composite porous carbon fiber membrane. Through the synthesis route of thermal chemical vapor deposition (T-CVD), the synthesis process is optimized and a multi-level three-dimensional network structure of carbon nanofibers and vertical graphene is constructed to enhance the conductivity of the silicon-carbon negative electrode material and accelerate carrier transport. On the one hand, the growing carbon nanofibers and vertical graphene form a multi-layer integrated three-dimensional network structure on the surface of the silicon-based material, which not only tightly covers the nano-silicon-based material, but also can effectively alleviate the volume expansion of the silicon-based material during the lithium insertion process; and firmly anchors the nano-silicon-based material in the porous carbon fiber substrate, which is beneficial to increase the loading capacity of the nano-silicon-based material, and is beneficial to improve the interface contact performance between the silicon-based material and the carbon material, improve the carrier transport, and improve the structure and cycle stability of the silicon-carbon negative electrode material. In addition, vertical graphene (VGs) and carbon nanofibers (CNFs) have significant mechanical strength, excellent chemical stability and high conductivity, and have significant advantages in slowing down the volume expansion of nano-silicon-based materials, promoting the stable formation of solid electrolyte interface phases, and improving the conductivity of silicon-carbon negative electrode materials.

[0040] The present application silicon-carbon negative electrode material includes a porous carbon fiber substrate and a nano silicon-based material loaded in the porous carbon fiber substrate, and the surface of the nano silicon-based material is coated with carbon nanofibers and vertical graphene. Among them, vertical graphene (VGs) and carbon nanofibers (CNFs) have significant mechanical strength, excellent chemical stability and high conductivity, and have significant advantages in slowing down the volume expansion of nano silicon-based materials, promoting the stable formation of solid electrolyte interface phases, and improving the conductivity of silicon-carbon negative electrode materials. In addition, carbon nanofibers and vertical graphene construct a multi-level three-dimensional network structure on the surface of silicon-based materials, tightly coating nano silicon-based materials, and suppressing the volume change of silicon-based materials during charge and discharge. At the same time, the three-dimensional network structure can firmly anchor the nano silicon-based material in the porous carbon fiber substrate, improve the high area capacity of the nano silicon-based material, and improve the electrochemical properties such as the structure and cycle stability, electrical conductivity, and stability of the SEI film of the silicon-carbon negative electrode material.

[0041] The negative electrode sheet of the present application includes the above-mentioned silicon-carbon negative electrode material, which has the characteristics of small volume change during charge and discharge, high structural stability, high conductivity, and is conducive to promoting the stable formation of the solid electrolyte interface phase. Therefore, the negative electrode sheet has high electronic conductivity and specific surface area, high negative electrode sheet capacity, promotes the rapid transmission of electrons and lithium ions, high cycle stability, and is conducive to improving the stability of the solid electrolyte interface.

[0042] The secondary battery of the present application comprises the above-mentioned negative electrode sheet with high capacity, high conductivity and good cycle stability, so that the secondary battery has high energy density, rate performance, cycle life and other characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0044] Figure 1 It is a schematic diagram of a process for preparing a silicon-carbon negative electrode material provided in an embodiment of the present application;

[0045] Figure 2 1 is a schematic flow chart of a method for preparing a silicon-carbon negative electrode material provided in Example 1 of the present application;

[0046] Figure 3 This is an overall SEM image of the silicon-carbon negative electrode material provided in Example 1 of the present application;

[0047] Figure 4 is a SEM image of a cross section of a fiber in the silicon-carbon negative electrode material provided in Example 1 of the present application;

[0048] Figure 5 This is a TEM image of the silicon-carbon negative electrode material provided in Example 1 of the present application;

[0049] Figure 6 is the XRD spectrum of the silicon-carbon negative electrode material provided in Example 1 of the present application;

[0050] Figure 7 It is the Raman spectrum of the silicon-carbon negative electrode material provided in Example 1 of the present application;

[0051] Figure 8 This is the full battery cycle stability curve of the silicon-carbon negative electrode material provided in Example 1 of the present application. DETAILED DESCRIPTION

[0052] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0053] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0054] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0055] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0056] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0057] The weight of the relevant components mentioned in the embodiments of the present specification can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components in the embodiments of the present specification is proportionally enlarged or reduced, it is within the scope disclosed in the embodiments of the present specification. Specifically, the mass described in the embodiments of the present specification can be μg, mg, g, kg and other mass units known in the chemical industry.

[0058] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0059] The first aspect of the present application provides a method for preparing a silicon-carbon negative electrode material, as shown in the attached Figure 1 As shown, the following steps are included:

[0060] S10. Preparing a porous carbon fiber membrane loaded with a metal catalyst;

[0061] S20. Prepare a dispersion of nano-silicon-based materials, so that the nano-silicon-based materials are distributed in the porous carbon fiber membrane to obtain a composite porous carbon fiber membrane;

[0062] S30. In an inert atmosphere containing a carbon source, the composite porous carbon fiber membrane is subjected to thermal chemical vapor deposition to grow carbon nanofibers and vertical graphene on the surface of the composite porous carbon fiber membrane to obtain a silicon-carbon negative electrode material.

[0063] The preparation method of the silicon-carbon negative electrode material provided in the first aspect of the embodiment of the present application is to prepare a porous carbon fiber membrane loaded with a metal catalyst, and then distribute the nano-silicon-based material into the porous carbon fiber membrane to form a composite porous carbon fiber membrane with a double layer of metal catalyst and nano-silicon-based material. Then, in an inert atmosphere containing a carbon source, the composite porous carbon fiber membrane is subjected to thermal chemical vapor deposition to grow carbon nanofibers (CNFs) and vertical graphene (VGs) on the surface of the composite porous carbon fiber membrane. Through the synthesis route of thermal chemical vapor deposition (T-CVD), the synthesis process is optimized and a multi-level three-dimensional network structure of carbon nanofibers and vertical graphene is constructed to enhance the conductivity of the silicon-carbon negative electrode material and accelerate carrier transport. On the one hand, the growing carbon nanofibers and vertical graphene form a multi-layer integrated three-dimensional network structure on the surface of the silicon-based material, which not only tightly covers the nano-silicon-based material, but also can effectively alleviate the volume expansion of the silicon-based material during the lithium insertion process; and firmly anchors the nano-silicon-based material in the porous carbon fiber substrate, which is beneficial to increase the loading capacity of the nano-silicon-based material, and is beneficial to improve the interface contact performance between the silicon-based material and the carbon material, improve the carrier transport, and improve the structure and cycle stability of the silicon-carbon negative electrode material. In addition, vertical graphene (VGs) and carbon nanofibers (CNFs) have significant mechanical strength, excellent chemical stability and high conductivity, and have significant advantages in slowing down the volume expansion of nano-silicon-based materials, promoting the stable formation of solid electrolyte interface phases, and improving the conductivity of silicon-carbon negative electrode materials.

[0064] In the above step S10:

[0065] In some possible implementations, the steps of preparing a porous carbon fiber membrane loaded with a metal catalyst include: preparing a solution of a metal catalyst, infiltrating a porous carbon fiber substrate into the solution of the metal catalyst, and drying to obtain a porous carbon fiber membrane loaded with a metal catalyst. In this case, after the metal catalyst is prepared into a solution, the porous carbon fiber substrate is infiltrated so that the metal catalyst can be uniformly loaded into the porous carbon fiber substrate to obtain a porous carbon fiber membrane uniformly loaded with a metal catalyst.

[0066] In some possible implementations, the metal catalyst includes at least one of a cobalt catalyst, a nickel catalyst, a copper catalyst, and a platinum catalyst. These metal catalysts can catalyze the growth of carbon nanofibers and vertical graphene in a subsequent thermal chemical vapor deposition process.

[0067] In some possible implementations, the metal catalyst includes at least one of cobalt catalysts selected from cobalt acetylacetonate, cobalt acetate, and cobalt chloride. In this case, the metal catalyst is a cobalt catalyst. On the one hand, cobalt has good catalytic activity and can effectively promote the growth of graphene; on the other hand, cobalt has good thermal stability and is suitable for T-CVD vertical graphene growth under high temperature conditions. In addition, the cobalt catalyst has a low cost and has a cost advantage.

[0068] In some possible implementations, the concentration of the metal catalyst solution is 40 mg / mL to 60 mg / mL, specifically 40 mg / mL, 45 mg / mL, 50 mg / mL, 55 mg / mL, 60 mg / mL, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values. In other embodiments, in the metal catalyst solution, the mass percentage of the metal catalyst is 5% to 20%, specifically 5%, 10%, 15%, 20%, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values. The concentration of the metal catalyst solution in the above-mentioned embodiment of the present application fully ensures the loading amount of the metal catalyst in the porous carbon fiber substrate, ensuring that there is sufficient metal catalyst in the porous carbon fiber membrane to catalyze the growth of carbon nanofibers and vertical graphene in the subsequent T-CVD process.

[0069] In some possible implementations, the solvent in the metal catalyst solution includes at least one of methanol, ethanol, acetone, benzene, isopropanol, and n-hexane. These solvents have good dissolution and dispersion effects on the metal catalyst, ensuring the solution stability of the metal catalyst, and facilitating the uniform and high-load loading of the metal catalyst into the porous carbon fiber substrate through infiltration treatment.

[0070] In some possible implementations, the porous carbon fiber substrate includes at least one of carbon felt, graphite paper, graphite plate, and carbon fiber cloth; these carbon substrates all have a porous structure, which is conducive to the loading of metal catalysts and nano-silicon-based materials. In some specific embodiments, the porous carbon fiber substrate is selected from carbon felt, which has a rich 3D network structure, which is more conducive to the loading of metal catalysts and nano-silicon-based materials.

[0071] In some possible implementations, the fiber diameter in the porous carbon fiber substrate is 5μm to 15μm; in this case, it is conducive to forming a suitable and rich pore structure in the porous carbon fiber substrate, ensuring that the carbon substrate has a rich three-dimensional porous structure, which is conducive to the loading of metal catalysts and nano-silicon-based materials to prepare silicon-carbon negative electrode materials. Exemplarily, the fiber diameter in the porous carbon fiber substrate can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc., typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values.

[0072] In some embodiments, the porous carbon fiber substrate is selected from carbon felt, and the diameter of the fibers in the carbon felt is 5 μm to 15 μm.

[0073] In some possible implementations, the thickness of the porous carbon fiber membrane is 0.5 mm to 1.5 mm; in this case, the thickness of the porous carbon fiber membrane not only provides a suitable conductive carrier for the high load of nano-silicon-based materials, but also ensures the thickness of the silicon-carbon negative electrode material, thereby ensuring the thickness of the silicon-carbon negative electrode material when used as a negative electrode sheet, so that the electrode sheet has a suitable application thickness. Exemplarily, the thickness of the porous carbon fiber membrane can be 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, etc., typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values.

[0074] In the above step S20:

[0075] In some possible implementations, the preparation of the composite porous carbon fiber membrane includes the steps of: preparing a dispersion of nano silicon-based materials, distributing the nano silicon-based materials in the dispersion into the porous carbon fiber membrane by filtering, and obtaining the composite porous carbon fiber membrane. In this case, distributing the nano silicon-based materials in the dispersion into the porous carbon fiber membrane by filtering can improve the uniformity of the loading of the nano silicon-based materials, and can flexibly control the loading amount and improve the loading efficiency.

[0076] In some embodiments, the preparation of the composite porous carbon fiber membrane includes the steps of: preparing a dispersion of nano silicon-based materials, loading the nano silicon-based materials in the dispersion into the porous carbon fiber membrane by vacuum filtration, and repeatedly filtering both sides of the porous carbon fiber membrane to ensure that the nano silicon-based materials are fully and evenly loaded into the porous carbon fiber membrane. After filtration, drying in a vacuum oven at a temperature of 60°C to 90°C to obtain a composite porous carbon fiber membrane.

[0077] In some possible implementations, the solvent in the dispersion of the nano-silicon-based material includes methanol (CH3OH), ethanol (C2H5OH), acetone (C3H6O), benzene (C6H6), isopropanol (C3H7OH), n-hexane (C6H 14 ) at least one of these solvents; these solvents all have high dispersibility for nano silicon-based materials. In some specific embodiments, the solvent is ethanol, which has good dispersibility for nano silicon-based materials, is safe and cheap, and is also convenient for subsequent drying.

[0078] In some possible implementations, in the dispersion of nano silicon-based materials, the mass percentage of nano silicon-based materials is 5% to 50%. In this case, the dispersion stability of the nano silicon-based materials in the dispersion is ensured, and it is also beneficial to load the nano silicon-based materials into the porous carbon fiber membrane through the filtering treatment unit. Exemplarily, in the dispersion of nano silicon-based materials, the mass percentage of nano silicon-based materials can be 5%, 10%, 20%, 30%, 40%, 50%, etc., typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values.

[0079] In some possible implementations, the nano silicon-based material includes at least one of elemental silicon, silicon oxide, and silicon carbide; these silicon-based materials all have relatively high capacity.

[0080] In some possible implementations, the particle size D50 of the nano silicon-based material is 30nm to 200nm. The particle size of the nano silicon-based material in the embodiment of the present application directly affects its surface area and availability in the electrochemical reaction. Silicon-based materials with smaller particle sizes have a larger specific surface area, can provide more active reaction sites, and are conducive to the rapid ion transport and efficient reaction of electrode materials during the insertion / extraction of lithium ions. In addition, silicon-based materials with smaller particle sizes are conducive to reducing stress and cracks between materials during expansion, thereby improving the cycle stability and long-term service life of the materials. At the same time, silicon-based materials with smaller particle sizes help to form a more uniform and continuous electronic conduction network, reduce resistance losses, and improve the conductivity and power performance of the electrode. Therefore, the particle size of silicon-based materials with a particle size D50 of 30nm to 200nm is relatively uniform, which is conducive to forming a uniform electrode layer and improving the consistency and stability of the electrode. In addition, silicon-based materials within this particle size range have a higher reaction rate during the insertion / extraction of lithium ions, and can achieve a faster electrochemical reaction kinetic response, thereby improving the charge and discharge performance of the battery. Compared with silicon-based materials with larger particle sizes, 30-200nm silicon-based materials can more effectively alleviate the stress caused by volume expansion and improve the cycle stability and cycle life of electrode materials.

[0081] Exemplarily, the particle size D50 of the nano-silicon-based material can be 30 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, or any other typical but non-limiting point value or an interval value between any two point values.

[0082] In some possible implementations, the loading amount of the nano-silicon-based material in the composite porous carbon fiber membrane is 1 mg / cm 2 ~40mg / cm 2 In this case, the loading amount of nano-silicon-based materials in the composite porous carbon fiber membrane can be flexibly adjusted from low loading to high loading. In some embodiments, the loading amount of nano-silicon-based materials in the composite porous carbon fiber membrane can reach 30 mg / cm 2 ~40mg / cm 2 The ultra-high silicon loading capacity significantly increases the silicon loading capacity of the silicon-carbon negative electrode material, thereby increasing the capacity of the silicon-carbon negative electrode.

[0083] For example, in the composite porous carbon fiber membrane, the loading amount of the nano-silicon-based material can be 1 mg / cm 2 , 5mg / cm 2 、10mg / cm 2 、15mg / cm 2 , 20mg / cm 2 , 25mg / cm 2 、30mg / cm 2、35mg / cm 2 , 40mg / cm 2 Typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values.

[0084] In the above step S30:

[0085] In some possible implementations, in the inert atmosphere, the carbon source includes at least one of ethanol, acetone, benzene, methanol, isopropanol, and n-hexane; these carbon sources can all trigger the growth of vertical graphene and carbon nanofibers.

[0086] In some possible implementations, the inert atmosphere includes at least one inert gas selected from argon, nitrogen, and helium. These inert gases can not only discharge non-reactive gas components in the reaction system to improve the reaction purity, but also can regulate the content of the carbon source and etching gas to improve the growth efficiency of carbon nanofibers and vertical graphene.

[0087] In some possible implementations, the inert atmosphere also contains an etching gas. In some possible implementations, the etching gas includes at least one of hydrogen, oxygen, and hydrogen fluoride. In this case, the etching gas can regulate the amount of carbon atoms deposited, thereby achieving a structure of vertically oriented growth of graphene nanosheets, and flexible vertical graphene nanosheets in silicon-carbon composite particles form a high-strength conductive network with directional channels, forming a conductive network with high mechanical strength, structural stability, and a developed and robust structure, thereby improving the conductivity of the silicon-carbon negative electrode and suppressing the volume expansion effect of silicon-based materials.

[0088] In some possible implementations, in an inert atmosphere, the flow rate of the inert gas is 100 mL / min to 180 mL / min; the flow rate of the carbon source gas is 100 mL / min to 180 mL / min; and the flow rate of the etching gas is 100 mL / min to 150 mL / min. In this case, the flow rate of the inert gas can better improve the reaction purity, regulate the content of the carbon source gas and the etching atmosphere, and improve the growth efficiency of carbon nanofibers and vertical graphene. The gas flow rate of the carbon source can better induce the growth of carbon nanofibers and vertical graphene. The flow rate of the etching gas is conducive to strengthening the growth of vertical graphene, while avoiding the formation of by-products and improving the purity of the product.

[0089] Exemplarily, in the inert atmosphere, the flow rate of the inert gas can be 100 mL / min, 110 mL / min, 120 mL / min, 130 mL / min, 150 mL / min, 160 mL / min, 170 mL / min, 180 mL / min, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values; the gas flow rate of the carbon source can be 100 mL / min, 110 mL / min, 120 mL / min, 130 mL / min, 150 mL / min, 160 mL / min, 170 mL / min, 180 mL / min, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values; the flow rate of the etching gas can be 100 mL / min, 110 mL / min, 120 mL / min, 130 mL / min, 140 mL / min, 150 mL / min, etc., typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0090] In some possible implementations, the heating rate of thermal chemical vapor deposition is 5°C / min to 10°C / min, the holding temperature is 1000°C to 1200°C, and the holding time is 6h to 12h. Under such conditions, the carbon source gas can be decomposed steadily, initiating the growth of carbon nanofibers and vertical graphene, and ensuring that the carbon nanofibers and vertical graphene grow fully on the surface of the silicon-based material to form a 3D multi-level network structure.

[0091] Exemplarily, the heating rate of thermal chemical vapor deposition can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values; the holding temperature can be 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values; the reaction time can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc., typical but non-limiting arbitrary point values, or an interval value between any two point values.

[0092] In some possible implementations, the steps are also included: after growing carbon nanofibers and vertical graphene, naturally cooling to 600°C to 900°C, and performing a nitrogen doping reaction with a nitrogen source gas to obtain a nitrogen-doped silicon-carbon negative electrode material. In this case, by introducing a nitrogen source gas to nitrogen-dope the silicon-carbon negative electrode material, the wettability of the electrolyte to the silicon-carbon negative electrode material is enhanced, and the electrical conductivity of the silicon-carbon negative electrode material is further improved. Exemplarily, the temperature condition of the nitrogen doping reaction can be 600°C, 700°C, 800°C, 900°C, and other typical but non-restrictive arbitrary point values ​​or interval values ​​between any two point values.

[0093] In some possible implementations, the nitrogen source gas includes at least one of ammonia, nitric oxide, and urea; these nitrogen source gases can be doped into the silicon-carbon negative electrode material under high temperature conditions of 600° C. to 900° C.

[0094] In some possible implementations, the flow rate of the nitrogen source gas is 15 mL / min to 25 mL / min. In this case, the flow rate of the nitrogen source gas can fully ensure the nitrogen doping effect on the silicon-carbon negative electrode material. Exemplarily, the flow rate of the nitrogen source gas can be 15 mL / min, 18 mL / min, 20 mL / min, 22 mL / min, 25 mL / min, and other typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0095] In some possible implementations, the duration of the nitrogen doping reaction is 20 minutes to 40 minutes; under this reaction duration condition, sufficient doping modification of the silicon-carbon negative electrode material can be ensured. Exemplarily, the duration of the doping reaction can be 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, and other typical but non-limiting arbitrary point values ​​or interval values ​​between any two point values.

[0096] In some possible implementations, the step of thermal chemical vapor deposition includes: under the condition of an inert gas flow rate of 100mL / min to 180mL / min, heating to 1000℃ to 1200℃ at a heating rate of 5℃ / min to 10℃ / min, introducing a carbon source and an etching gas and keeping the temperature for 6h to 12h to grow carbon nanofibers and vertical graphene; naturally cooling to 600℃ to 900℃, introducing a nitrogen source gas at a flow rate of 15mL / min to 25mL / min to react for 20min to 40min to obtain a nitrogen-doped silicon-carbon negative electrode material.

[0097] In a second aspect, an embodiment of the present application provides a silicon-carbon negative electrode material, comprising a porous carbon fiber substrate and a nano-silicon-based material loaded in the porous carbon fiber substrate, wherein the surface of the nano-silicon-based material is coated with carbon nanofibers and vertical graphene.

[0098] The silicon-carbon negative electrode material of the embodiment of the present application includes a porous carbon fiber substrate and a nano-silicon-based material loaded in the porous carbon fiber substrate, and the surface of the nano-silicon-based material is coated with carbon nanofibers and vertical graphene. Among them, vertical graphene (VGs) and carbon nanofibers (CNFs) have significant mechanical strength, excellent chemical stability and high electrical conductivity, and have significant advantages in slowing down the volume expansion of nano-silicon-based materials, promoting the stable formation of solid electrolyte interface phases, and improving the electrical conductivity of silicon-carbon negative electrode materials. In addition, carbon nanofibers and vertical graphene construct a multi-level three-dimensional network structure on the surface of silicon-based materials, which not only makes the silicon-carbon negative electrode material have high electronic conductivity and specific surface area, but also promotes the interaction between electrons and Li+ The three-dimensional network structure can not only quickly transmit the nano-silicon-based materials, but also tightly wrap the nano-silicon-based materials, inhibiting the volume change of the silicon-based materials during the charge and discharge process. At the same time, the three-dimensional network structure can firmly anchor the nano-silicon-based materials in the porous carbon fiber substrate, improve the high area capacity of the nano-silicon-based materials, and improve the structure and cycle stability, conductivity, stability of the SEI film and other electrochemical properties of the silicon-carbon negative electrode materials.

[0099] The silicon-carbon negative electrode material of the embodiment of the present application can be prepared by the method of the embodiment described above.

[0100] In some embodiments, the silicon-carbon negative electrode material has self-supporting properties and has the characteristics of good structural stability, good cycle stability, high electrical conductivity, etc. It can be directly applied to the battery as a negative electrode sheet without the need for additional auxiliary materials such as binders and conductive agents, and no additional current collector is required.

[0101] In some possible implementations, in the silicon-carbon negative electrode material, the particle size D50 of the nano-silicon-based material is 30 nm to 200 nm.

[0102] In some possible implementations, in the silicon-carbon negative electrode material, the fiber diameter is 5 μm to 15 μm.

[0103] In some possible implementations, the thickness of the silicon-carbon negative electrode material is 0.5 mm to 1.5 mm.

[0104] In some possible implementations, the nano silicon-based material includes at least one of elemental silicon, silicon oxide, and silicon carbide; these silicon-based materials all have relatively high capacity.

[0105] In some possible implementations, the loading amount of nano-silicon-based materials in the silicon-carbon negative electrode material is 1 mg / cm 2 ~40mg / cm 2 .

[0106] In some possible implementations, in the silicon-carbon negative electrode material, the mass percentage of the porous carbon fiber substrate is 60% to 70%; the total mass percentage of the carbon nanofibers and the vertical graphene is 10% to 20%.

[0107] The beneficial effects of the above embodiments of the present application have been discussed in the previous text and will not be repeated here.

[0108] In a third aspect, an embodiment of the present application provides a negative electrode sheet, which includes the silicon-carbon negative electrode material prepared by the above method, or the above silicon-carbon negative electrode material.

[0109] The negative electrode sheet of the embodiment of the present application includes the above-mentioned silicon-carbon negative electrode material, which has the characteristics of small volume change during charge and discharge, high structural stability, high conductivity, and is conducive to promoting the stable formation of the solid electrolyte interface phase. Therefore, the negative electrode sheet has high electronic conductivity and specific surface area, high negative electrode sheet capacity, promotes the rapid transmission of electrons and lithium ions, high cycle stability, and is conducive to improving the stability of the solid electrolyte interface.

[0110] In a fourth aspect, an embodiment of the present application provides a secondary battery, wherein the secondary battery comprises the negative electrode sheet described above.

[0111] The secondary battery of the embodiment of the present application includes the negative electrode sheet with high capacity, high conductivity and good cycle stability, so that the secondary battery has higher energy density, rate performance, cycle life and other characteristics.

[0112] The present application does not specifically limit the positive electrode sheet, electrolyte, separator, etc. in the secondary battery of the embodiment, and can be applied to any battery system.

[0113] In some possible implementations, the positive electrode sheet includes a current collector and a positive electrode active layer formed on a surface of the current collector.

[0114] In some possible implementations, the preparation of the positive electrode sheet includes the steps of: mixing the positive electrode material, the conductive agent and the binder to form an electrode slurry, coating the electrode slurry on the current collector, and preparing the positive electrode sheet through the steps of drying, rolling, die cutting, etc.

[0115] In some possible implementations, the mass percentage of the positive electrode material in the positive electrode active layer of the positive electrode sheet is 90% to 95%.

[0116] In some possible implementations, the current collector of the positive electrode sheet includes but is not limited to any one of copper foil and aluminum foil.

[0117] In some possible implementations, the content of the binder in the active material layer of the positive electrode sheet is 2 wt % to 5 wt %.

[0118] In some possible implementations, the binder includes one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives.

[0119] In some possible implementations, the content of the conductive agent in the active material layer of the positive electrode sheet is 1 wt % to 5 wt %.

[0120] In some possible implementations, the conductive agent includes graphite, carbon black, acetylene black, graphene, carbon fiber, C 60and one or more of carbon nanotubes.

[0121] In some possible implementations, the separator can block the passage of electrons and allow the passage of ions. Exemplarily, the separator includes, but is not limited to, at least one material selected from polypropylene fiber, polyacrylonitrile fiber, polyvinyl formal fiber, poly(ethylene terephthalate), polyethylene terephthalate, polyamide fiber, and poly(p-phenylene terephthalamide).

[0122] In some possible implementations, the electrolyte includes at least one soluble metal salt. In some specific embodiments, the metal salt includes LiClO4, LiBF4, LiPF6, LiAsF6, LiCF3SO3, LiTDI, Li[(CF3SO2)2N], Li[(FSO2)2N], Li[(C m F 2m+1 SO2)(C n F 2n+1 SO2)N], wherein m and n are natural numbers. These electrolytic salts can ensure high ionic conductivity of the electrolyte, and do not cause harmful side reactions with electrode materials, electrolytes, diaphragms, etc., and have good chemical stability.

[0123] In some possible implementations, the secondary battery includes at least one of a battery cell, a battery module, and a battery pack.

[0124] In some possible implementations, the battery cell types include lithium-ion batteries, as well as new batteries such as lithium-air batteries and lithium metal batteries.

[0125] In some possible implementations, the battery cells of the embodiments of the present application can be assembled into a battery module, and the number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module. Further, the battery module can also include a housing with a storage space, and multiple battery cells are stored in the storage space.

[0126] In a possible implementation, the battery cells and / or battery modules may also be assembled into a battery pack, and the number of battery cells or battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0127] In order to enable the above implementation details and operations of the present application to be clearly understood by those skilled in the art, as well as to significantly demonstrate the improved performance of the silicon-carbon negative electrode material and its preparation method and application in the embodiments of the present application, the above technical scheme is illustrated by means of multiple embodiments below.

[0128] Example 1

[0129] A silicon-carbon negative electrode material, such as Figure 2As shown, its preparation comprises the following steps:

[0130] 1. Preparation of porous carbon fiber membrane loaded with metal catalyst: prepare 50 mg / mL of cobalt acetylacetonate (Co(C5H7O2)2) ethanol solution, and soak carbon felt CF with a thickness of 1 mm, a fiber diameter of 10 μm, and a porosity of 50% in the solution for 2 h to ensure uniform loading of the catalyst. Then take out the CF and place it in an oven at 80°C for air drying to obtain a porous carbon fiber membrane.

[0131] 2. Loading silicon nanoparticles: prepare an ethanol dispersion of Si nanoparticles (SiNPs) with a mass percentage of 40%, introduce the Si nanoparticles into the porous carbon fiber membrane by vacuum filtration, control the vacuum filtration time to 30 min and the volume of the Si nanoparticle ethanol dispersion to 100 ml to control the load, repeat filtration on both sides to ensure uniform loading of the Si nanoparticles, dry in a vacuum oven at 80°C, cut into fixed sizes for use, and obtain a composite porous carbon fiber membrane, marked as CF / Si.

[0132] 3. T-CVD process: The composite porous carbon fiber membrane prepared in the previous step is placed in the center area of ​​the furnace, and then the furnace tube is purged with argon (Ar) to remove air, with a flow rate of 180mL / min. The temperature is raised to 1000℃ in an Ar atmosphere under ambient pressure and then kept constant at a heating rate of 5℃ / min. The argon flow rate is maintained at 100mL / min, and then Ar / C2H5OH mixed gas is added to grow carbon nanofibers VGs / vertical graphene CNFs on the CF / Si surface at the same flow rate. The growth process includes the introduction of H2 / Ar at a flow rate of 125±5mL / min. The CF / Si composite material is kept at the desired temperature for 12 hours to promote the growth of VGs and CNFs. As VGs and CNFs grow, the furnace is naturally cooled to 900℃. Then, ammonia gas was introduced at a flow rate of 20 mL / min for 30 min to dope N into the silicon-carbon negative electrode material, labeled as CF@Si@CNFs@VGs electrode, where the loading amount of silicon material was 40 mg / cm 2 .

[0133] Example 2

[0134] A silicon-carbon negative electrode material, which differs from Example 1 in that the loading amount of the prepared electrode nano-Si is smaller, about 50% of that in Example 1, and the loading amount of the silicon material is 20 mg / cm 2 , the other steps remain unchanged.

[0135] Example 3

[0136] A silicon-carbon negative electrode material, which differs from Example 1 in that the loading amount of the prepared electrode nano-Si is smaller, about 25% of that in Example 1, and the loading amount of the silicon material is 10 mg / cm 2 , the other steps remain unchanged.

[0137] Example 4

[0138] A silicon-carbon negative electrode material, which differs from Example 1 in that the loading amount of the prepared electrode nano-Si is smaller, about 13% of that in Example 1, and the loading amount of the silicon material is 5 mg / cm 2 , the other steps remain unchanged.

[0139] Example 5

[0140] A silicon-carbon negative electrode material, which differs from Example 1 in that the type of metal catalyst used is different, the cobalt acetylacetonate in step 1 is replaced by nickel chloride, and other steps remain unchanged.

[0141] Example 6

[0142] A silicon-carbon negative electrode material, which differs from Example 1 in that the type of metal catalyst used is different, the cobalt acetylacetonate in step 1 is replaced by cupric chloride, and other steps remain unchanged.

[0143] Example 7

[0144] A silicon-carbon negative electrode material, which differs from Example 1 in that the type of metal catalyst used is different, the cobalt acetylacetonate in step 1 is replaced by platinum chloride, and other steps remain unchanged.

[0145] Example 8

[0146] A silicon-carbon negative electrode material, which differs from Example 1 in that the type of silicon-based material used is different, the Si nanoparticles in step 2 are replaced by silicon oxide, and other steps remain unchanged.

[0147] Example 9

[0148] A silicon-carbon negative electrode material, which differs from Example 1 in that the type of silicon-based material used is different, the Si nanoparticles in step 2 are replaced by silicon carbide, and other steps remain unchanged.

[0149] Example 10

[0150] A silicon-carbon negative electrode material, which differs from Example 1 in that the insulation temperature of T-CVD is different, the insulation temperature in step 3 is replaced from 1000° C. to 950° C., and other steps remain unchanged.

[0151] Embodiment 11

[0152] A silicon-carbon negative electrode material, which differs from Example 1 in that the insulation temperature of T-CVD is different, the insulation temperature in step 3 is replaced from 1000° C. to 1200° C., and other steps remain unchanged.

[0153] Example 12

[0154] A silicon-carbon negative electrode material, which differs from Example 1 in that the insulation temperature of T-CVD is different, the insulation temperature in step 3 is replaced from 1000° C. to 1250° C., and other steps remain unchanged.

[0155] Embodiment 13

[0156] A silicon-carbon negative electrode material, which differs from Example 1 in that no nitrogen doping operation is performed and other steps remain unchanged.

[0157] Comparative Example 1

[0158] A silicon-carbon negative electrode material, which differs from Example 1 in that: SiNPs are not treated in any way, and a slurry consisting of SiNPs, carbon black, styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) is directly coated on a copper foil to prepare a working electrode, and then vacuum dried at 100°C for 12 hours. The weight of each electrode is 0.8-1.5 mg cm -2 The other test steps remain unchanged.

[0159] Comparative Example 2

[0160] A silicon-carbon negative electrode material, which differs from Example 1 in that the T-CVD process is not performed to grow VGs and CNFs, and other steps are unchanged.

[0161] Comparative Example 3

[0162] A silicon-carbon negative electrode material, which differs from Example 1 in that: in step 3, VGs and CNFs are not grown in situ, but the composite porous carbon fiber membrane is directly mixed with VGs and CNFs, and other steps remain unchanged.

[0163] Comparative Example 4

[0164] A silicon-carbon negative electrode material, which differs from Example 1 in that: in step 1, no metal catalyst is loaded in the porous carbon fiber membrane, in step 3, no metal catalyst is used, only vertical graphene is grown, and no carbon nanofibers are generated, and other steps remain unchanged.

[0165] Further, in order to verify the progress of the embodiments of the present application, the silicon-carbon negative electrode materials prepared in the above embodiments and comparative examples were subjected to the following performance tests:

[0166] 1. The morphology of the silicon-carbon negative electrode material prepared in Example 1 was observed, and the test results are shown in the attached Figure 3 and 4 As shown in the scanning electron microscope image, Figure 3 The overall SEM image of CF@Si@CNFs@VGs is shown in Figure 2. Figure 4 This is the SEM image of the fiber cross section of CF@Si@CNFs@VGs. Figure 4 a is the overall SEM image of the fiber cross section of CF@Si@CNFs@VGs, Figure 4 b is the cross section of a single fiber. Figure 4 The c cross-sectional view in the figure is a locally enlarged SEM image of vertical graphene. Figure 4 d in the figure is a partially enlarged SEM image of the CNFs@VGs network in the cross-sectional view. The CNFs and VG grown in the silicon-carbon negative electrode material prepared in the embodiment of the present application are interconnected with the carbon felt fibers to form a multi-level three-dimensional network structure.

[0167] 2. The silicon-carbon negative electrode material prepared in Example 1 was tested by transmission electron microscopy. The test results are shown in the attached figure. Figure 5 As shown in the TEM image of CF@Si@CNFs@VGs, it can be seen that rich carbon materials are grown on Si particles, and these carbon materials have obvious characteristics of multi-layer vertical graphene.

[0168] 3. The silicon-carbon negative electrode material prepared in Example 1 was subjected to an X-ray diffraction test. The test results are shown in the attached figure. Figure 6 As shown in the XRD diagram, it can be seen that the silicon-carbon negative electrode material prepared in the embodiment of the present application contains characteristic peaks of both carbon and silicon.

[0169] 4. The silicon-carbon negative electrode material prepared in Example 1 was subjected to Raman diffraction test. The test results are shown in the attached figure. Figure 7 As shown in the Raman diagram, it can be seen that the Raman spectrum confirms the successful synthesis of graphene, which can be seen from the 1340cm -1 (D belt), 1581cm -1 (G band) and 2680cm -1 This is evidenced by the characteristic signal of (2D band).

[0170] 5. The above-mentioned embodiments and comparative examples were tested for the performance of the negative electrode of lithium-ion batteries: the prepared silicon-carbon negative electrode material was cut into small discs with a diameter of 12 mm by a slicer, weighed and recorded, and the weighed electrode pieces were dried in a vacuum drying oven at 85°C for 12 hours to remove moisture. The battery was assembled in a glove box filled with an argon atmosphere, and a 2032 button half-cell was produced. The negative electrode material was the 12 mm disc cut in the above steps, the diaphragm was Celgard 2400, the lithium sheet was the counter electrode and the reference electrode, and the electrolyte was 1M lithium hexafluorophosphate (LiPF6) dissolved in a mixed solution of ethylene carbonate (EC), dimethyl carbonate (DMC) and dimethyl carbonate (DEC) in a volume ratio of 1:1:1. The electrochemical performance was evaluated using a Neware battery test system at 30°C, in a voltage range of 0.005-2.0V (relative to Li / Li+) and at different current densities. An electrochemical workstation (CHI760D) was used at 10 5 ~10 -2 Cyclic voltammetry (CV) curves and electrochemical impedance spectroscopy (EIS) curves were obtained at different scan rates in the Hz range with an amplitude of 5 mV.

[0171] The electrochemical performance test results are shown in Table 1 below:

[0172] Table 1

[0173]

[0174] Among them, in the silicon-carbon negative electrode material CF@Si@CNFs@VGs of Example 1, the loading amount of silicon material can reach 40 mg / cm 2 The cycle stability curve of the prepared full battery is shown in the attached Figure 8 As shown, it can be seen that the battery still exhibits a high capacity after 500 cycles and has good cycle stability.

[0175] From the above test results, it can be seen that the multi-level 3D network structure formed by the introduction of Co-based catalysts and the growth of CNFs and VGs by T-CVD process effectively slows down the volume expansion of Si during the charge and discharge cycle, while enhancing the electronic conductivity and ion transport efficiency of the electrode. N doping effectively improves the wettability to the electrolyte, so the silicon-carbon negative electrode material CF@Si@CNFs@VGs exhibits high capacity and better cycle stability.

[0176] By comparing Examples 1 to 4, it can be seen that the loading amount of silicon material is 1 to 40 mg / cm 2 , silicon-carbon negative electrode materials all show high cycle stability.

[0177] By comparing Example 1 with Examples 6 to 8, it can be seen that when the metal catalyst is a cobalt catalyst, it has a better catalytic effect and can better improve the capacity and cycle stability of the silicon-carbon negative electrode material.

[0178] By comparing Example 1 with Examples 8 to 9, it can be known that the silicon-based material in the embodiments of the present application can be nano-silicon alone, or can be silicon carbide, silicon oxide, and the like.

[0179] By comparing Example 1 with Examples 10 to 12, it can be seen that the T-CVD has a better sintering effect when the insulation temperature is 1000° C. to 1200° C., which can better improve the capacity and cycle stability of the silicon-carbon negative electrode material.

[0180] By comparing Example 1 and Example 13, it can be seen that nitrogen doping can better improve the capacity and cycle stability of the silicon-carbon negative electrode material.

[0181] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a silicon-carbon negative electrode material, characterized in that: The following steps are involved: preparing a porous carbon fiber membrane loaded with a metal catalyst; Preparing a dispersion of nano silicon-based materials to distribute the nano silicon-based materials into the porous carbon fiber membrane to obtain a composite porous carbon fiber membrane; In an inert atmosphere containing a carbon source, the composite porous carbon fiber membrane is subjected to thermal chemical vapor deposition to grow carbon nanofibers and vertical graphene on the surface of the composite porous carbon fiber membrane to obtain a silicon-carbon negative electrode material.

2. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: The step of preparing the porous carbon fiber membrane loaded with a metal catalyst comprises: preparing a solution of a metal catalyst, impregnating a porous carbon fiber substrate into the solution of the metal catalyst, and drying to obtain the porous carbon fiber membrane loaded with a metal catalyst; And / or, the metal catalyst includes at least one of a cobalt catalyst, a nickel catalyst, a copper catalyst, and a platinum catalyst.

3. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: The metal catalyst includes at least one cobalt catalyst selected from the group consisting of cobalt acetylacetonate, cobalt acetate, and cobalt chloride; And / or, the porous carbon fiber substrate includes at least one of carbon felt, graphite paper, graphite plate, and carbon fiber cloth; and / or, the concentration of the metal catalyst solution is 40 mg / mL to 60 mg / mL; And / or, the fiber diameter of the porous carbon fiber substrate is 5 μm to 15 μm; And / or, the thickness of the porous carbon fiber membrane is 0.5 mm to 1.5 mm; And / or, in the solution of the metal catalyst, the solvent includes at least one of methanol, ethanol, acetone, benzene, isopropanol, and n-hexane.

4. The method for preparing the silicon-carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation of the composite porous carbon fiber membrane comprises the steps of: preparing a dispersion of the nano silicon-based material, distributing the nano silicon-based material in the dispersion into the porous carbon fiber membrane by filtering, and obtaining the composite porous carbon fiber membrane; And / or, in the dispersion of the nano-silicon-based material, the solvent includes at least one of methanol, ethanol, acetone, benzene, isopropanol, and n-hexane; And / or, in the dispersion of the nano silicon-based material, the mass percentage of the nano silicon-based material is 5% to 50%; And / or, the nano silicon-based material includes at least one of elemental silicon, silicon oxide, and silicon carbide; And / or, the particle size D50 of the nano silicon-based material is 30nm to 200nm; And / or, in the composite porous carbon fiber membrane, the loading amount of the nano silicon-based material is 1 mg / cm 2 ~40mg / cm 2 .

5. The method for preparing the silicon-carbon negative electrode material according to claim 4, characterized in that: In the inert atmosphere, the carbon source includes at least one of ethanol, acetone, benzene, methanol, isopropanol, and n-hexane; And / or, the inert atmosphere includes at least one inert gas selected from argon, nitrogen and helium; And / or, the inert atmosphere further contains etching gas.

6. The method for preparing the silicon-carbon negative electrode material according to claim 5, characterized in that: The etching gas includes at least one of hydrogen, oxygen and hydrogen fluoride; And / or, in the inert atmosphere, the flow rate of the inert gas is 100 mL / min to 180 mL / min; the flow rate of the carbon source gas is 100 mL / min to 180 mL / min; the flow rate of the etching gas is 100 mL / min to 150 mL / min; And / or, the heating rate of the thermal chemical vapor deposition is 5°C / min to 10°C / min, the holding temperature is 1000°C to 1200°C, and the holding time is 6h to 12h; And / or, it also includes the steps of: after growing the carbon nanofibers and the vertical graphene, naturally cooling to 600° C. to 900° C., performing nitrogen doping reaction with nitrogen source gas to obtain nitrogen-doped silicon-carbon negative electrode material.

7. The method for preparing the silicon-carbon negative electrode material according to claim 6, characterized in that: The nitrogen source gas includes at least one of ammonia, nitric oxide and urea; And / or, the flow rate of the nitrogen source gas is 15 mL / min to 25 mL / min; And / or, the duration of the nitrogen doping reaction is 20 min to 40 min; And / or, the step of thermal chemical vapor deposition includes: under the condition that the flow rate of the inert gas is 100mL / min~180mL / min, after heating to 1000℃~1200℃ at a heating rate of 5℃ / min~10℃ / min, introducing the carbon source and the etching gas for 6h~12h to grow the carbon nanofibers and the vertical graphene; naturally cooling to 600℃~900℃, introducing the nitrogen source gas at a flow rate of 15mL / min~25mL / min to react for 20min~40min to obtain the nitrogen-doped silicon-carbon negative electrode material.

8. A silicon-carbon negative electrode material, characterized in that: The invention comprises a porous carbon fiber substrate and a nano silicon-based material loaded in the porous carbon fiber substrate, wherein the surface of the nano silicon-based material is coated with carbon nanofibers and vertical graphene.

9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a silicon-carbon negative electrode material prepared by the method according to any one of claims 1 to 7, or a silicon-carbon negative electrode material according to claim 8.

10. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Uniform carbon film and vertical graphene dual-coated silicon-carbon composite material, preparation method thereof and application in lithium ion battery

    CN109616630A

  • Graphene and carbon nanotube in-situ growth co-modification toughening carbon fiber preparation method

    CN110886089A

  • Silicon composite nanofiber, silicon composite nanofiber membrane and preparation method and application of silicon composite nanofiber membrane

    CN115966658A

  • Fiber carbon-silicon composite material and manufacturing method thereof

    CN116941062A

  • Method for producing anode for lithium secondary battery and anode composition, and lithium secondary battery

    WO2007004728A1